2019
DOI: 10.1016/j.mayocp.2019.10.010
|View full text |Cite
|
Sign up to set email alerts
|

VpALI—Vaping-related Acute Lung Injury: A New Killer Around the Block

Abstract: The use of electronic cigarettes, known as vaping, has become increasingly popular over the past decade, particularly in the adolescent and young adult population, often exposing users to harmful chemicals. Vaping has been associated with a heterogeneous group of pulmonary disease. Recently, a multistate epidemic has emerged surrounding vaping-related acute lung injury, prompting the Centers for Disease Control and Prevention to list an official health advisory. In this review, we describe the current literatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 85 publications
0
33
0
4
Order By: Relevance
“…To the authors knowledge at the time of publication there are 7 reviews on e-cigarette-related health effects and case reports, each specifically focusing on one aspect of the e-cigarette-related injury: The respiratory effects [18,19], poisonings [20], burn injuries [21,22], radiologic appearance of lung injuries [23], and histologic findings [24]. The majority of those reviews were published before the 2019 e-cigarette-related injury outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…To the authors knowledge at the time of publication there are 7 reviews on e-cigarette-related health effects and case reports, each specifically focusing on one aspect of the e-cigarette-related injury: The respiratory effects [18,19], poisonings [20], burn injuries [21,22], radiologic appearance of lung injuries [23], and histologic findings [24]. The majority of those reviews were published before the 2019 e-cigarette-related injury outbreak.…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, IL-6 has been shown to increase with exposure to any insult causing acute lung injury to maintain the homeostasis of the in ammatory response [36][37][38]. The increase in G-CSF and eotaxin along with the increase in CD4 cells in BALF suggest that acute exposure may be leaning toward the Th2 pathway, implicating potential eosinophilic pneumonia with prolonged exposure [39][40][41]. Excessive in ammation results in lung damage in diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The use of such e-cigarettes is called JUULing [7]. Between 2017 and 2018, JUULing increased from 11.7% to 20.8%; in 2018 3.7 million high school students were affected [11,12]. The observations about vaping in Europe and the United States gradually revealed vaping-associated complications, most commonly lung complications leading to acute respiratory failure (fatal in some cases) [13][14][15].…”
mentioning
confidence: 99%
“…According to American estimates, 700 various e-liquids were FIGURE 1. A diagram of e-cigarette (elaborated according to [9,12] Heating element (atomiser) Battery…”
mentioning
confidence: 99%
See 1 more Smart Citation